Ethnic Socialization, Ethnic Identity, and Self-Esteem in Chinese Mulao Adolescents - Kuang, Lu; Nishikawa, Saori (Frontiers in Psychology, 2021)
We examined the associations and likely pathways between ethnic socialization, ethnic identity, and self-esteem among junior high school students of Chinese Mulao ethnic minority. A total of 469 Mulao students (220 boys and 249 girls) completed the Ethnic Socialization Measurement revised by Yin et al. (2016), the Revised Multigroup Ethnic Identity Measure (MEIM-R) by Roberts et al. (1999), and Rosenberg’s Self-esteem Scale (Chinese Version) by Wang et al. (1999). The main results indicated that adolescents who perceived more promotion of harmony messages tended to report stronger ethnic identity and higher self-esteem. Adolescents who perceived cultural socialization displayed stronger ethnic identity and higher self-esteem, while the promotion of distrust messages was negatively associated with self-esteem. Multiple-group analysis revealed that the relationships were stable across gender, parental education, but varied significantly across students’ grade. These findings emphasize the important role of positive ethnic socialization messages in adolescents’ ethnic identity and self-esteem. In addition, it is also important that we pay attention to negative ethnic socialization messages and consider their grade when communicating ethnic information with adolescents. Finally, our results are analyzed and notable suggestions are presented for ethnic family education.